Proposed indicators for socio taqwa index indicator in Kelantan state Government - Fatinah Binti Mohd Azhar Nur (EDP Sciences, 2021)
The Kelantan state government has used the Developing with Islam policy to carry out its administration since 1990 in the state of kelantan. Various programs and changes have been implemented in 5 aspect which is in administration, shariah, economy, education and sociology. Since 1990, the Developing with Islam policy still ongoing. However, no comprehensive study has been conducted on all aspects of the Developing with Islam policy. Therefore, this study was conducted to produce appropriate indicators that will be used to see the effectiveness of the Developing with Islam policy in Kelantan. In this study paper will explain where these indicators are come from. By having this indicators, Kelantan state government can create an index and at the same time can evaluate the achievement of the policy since the policy was implemented. The result can help Kelantan state government to make improvement from time to time and become as a good example of Islamic state in Malaysia.